Joint amplitude and phase partition based physical layer key generation method - Nannan LI; Yu HAN; Ning GAO; Shi JIN (Dianxin kexue)
A key generation method based on wireless channel physical layer features is of great significance for improving security of wireless transmission.An orthogonal frequency division multiplexing (OFDM) communication system based on time division duplex (TDD) with multipath fading channels was considered.Utilizing the advantages of OFDM multicarrier and the channel reciprocity and combining the phase and amplitude information of channel frequency response (CFR), two algorithms for physical layer key generation were proposed.Theoretical analysis and experimental simulation show that the proposed algorithm has more consistent and smaller overhead in information negotiation, in addition, the proposed algorithm can increase the key length and enhance randomness, and has a better defense capability against eavesdropping and active attacks of the illegal user.